Endoglin-Aptamer-Functionalized Liposome-Equipped PD-1-Silenced T Cells Enhance Antitumoral Immunotherapeutic Effects - Xie S (Dove Medical Press, 2021)
Shenxia Xie,1,2,* Xiaoqiong Hou,1,3,* Wei Yang,1,3,* Wei Shi,1,3 Xiaomei Yang,1,3 Siliang Duan,3 Fengzhen Mo,3 Aiqun Liu,3 Wu Wang,1,4 Xiaoling Lu1,3,5 1School of Preclinical Medicine, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 2Pharmaceutical College, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 3International Nanobody Research Center of Guangxi, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 4Laboratory of Tropical Biomedicine and Biotechnology, School of Tropical Medicine and Laboratory Medicine, Hainan Medical University, Haikou, Hainan, 571101, People’s Republic of China; 5College of Stomatology, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoling LuCollege of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of ChinaEmail luxiaoling@gxmu.edu.cnWu WangLaboratory of Tropical Biomedicine and Biotechnology, School of Tropical Medicine and Laboratory Medicine, Hainan Medical University, Haikou, Hainan, 571101, People’s Republic of ChinaEmail lxd8860@163.comBackground: The broader application of adoptive cell therapy (ACT) in cancer immunotherapies (particularly for solid tumors) has always been limited by the immunosuppressive tumor microenvironment (TME) and the insufficient targetability of effector T cells, resulting in unsatisfied therapeutic outcome. Here, we designed a new strategy by using aptamer-based immunoliposomes to modify PD-1-silencing T cells, which were activated by dendritic cell (DC)/tumor fusion cells (FCs) to improve the antitumor potency of cytotoxic T lymphocytes (CTLs/CD8+ T cells).Methods: PD-1 gene was knocked out from CD8+ T cells using CRISPR/Cas9 system to liberate T cell activity from immunosuppression. The PD-1− T cells were stimulated with DC/tumor FCs, followed by further functional modification of tumor-specific nanoliposomes (hEnd-Apt/CD3-Lipo) to generate FC/PD-1− CTLs. The activation and proliferation and specificity of the modified FC/PD-1− CTLs were measured. The antitumor activity of these CTLs against HepG2-tumors was evaluated in xenograft NOD/SCID mice, and the antitumor mechanism was investigated based on tissue immunohistochemistry and serum ELISA.Results: Our results indicated that the modification of hEnd-Apt/CD3-Lipo nanocomposites on the FC/PD-1− CTLs had a more substantial synergetic effect in inhibiting tumor growth and prolonging animal survival, rather than other control liposomes. Furthermore, the hEnd-Apt/CD3-Lipo-modified FC/PD-1− CTLs showed a stronger antitumor outcome in the tumor-bearing mouse model, through the mechanisms of suppressing tumor cell proliferation, promoting tumor apoptosis, reducing angiogenesis but increasing the infiltration of the FC/PD-1− CTLs in the tumor tissue, as well as upregulating the systemic levels of IFN-γ, IL-2, TNF-α and IL-6 cytokines, by comparison of the control settings.Conclusion: In sum, our investigation suggests an enhancement of antitumor effect by the surface modification of endoglin-targeting nanoliposomes upon DC/tumor FC-activated PD-1− CTLs, therefore, provides a new tumoral endoglin-targeted approach as a promising strategy to reduce immunosuppression of tumor microenvironment and improve the immunotherapeutic outcome of anticancer ACT.Keywords: nanoliposome, PD-1, CRISPR/Cas9, endoglin, aptamer, antitumor immunotherapy